ANALISIS PENDAPATAN PEDAGANG KECIL SEBELUM DAN SESUDAH PEMBERIAN KREDIT PADA BANK BRI CABANG TENGGARONG UNIT TENGGARONG KOTA KABUPATEN KUTAI KARTANEGARA - -, Ermawati - (EKONOMIA, 2014)
The purpose of the study to determine small differences in income trader before and after the extension of credit at the bank BRI Branch Tenggarong Kutai regency. Summary of the study is whether earnings results in different small traders before and after the extension of credit in the bank BRI branch Tenggarong City Kutai. Basic theory used in this study Financial Management covers the meaning, purpose, people business credit, micro and small business income. From the results of research using formulas growth (growth) with Yt-1 that is income before using Credit of People with an average of Rp 3.338.095,238. and Y, is income after using Credit of People with an average of Rp 4542857.143 to create interval obtained Rp 1,204,761.90. Reveals that there is a difference, or rather positive growth in revenue after using Credit of Representatives with an average growth of 39.87% which indicates that the contribution of Bank BRI units Tenggarong have a positive value or it can be said as the higher earnings before using Credit of Representatives (KUR) then will the higher the income level changes that will be recovered operators micro and Small Enterprises (UMK in Sub Tenggarong will also increase)